The Power to Transform: The Kemano Power Project and the Debate about the Future of Northern British Columbia - Coates, Ken (Journal of Northern Studies, 2007)
The struggle to determine the pace and nature of resource development has long been at the centre of northern autonomy movements. The fortyyear-long debate over the Kemano Power Project in Northern British Columbia reveals how the understanding of hydro-development has shifted from a major regional benefit to a more complicated and conflicted view in which environmental and indigenous concerns are balanced against economic opportunities. When built in the 1950s, Kemano was seen as the foundation for a stable and prosperous industrial economy. The planned expansion of the hydro-electric system in the 1980s and 1990s touched off a major debate inside and outside the region. The region wrestled with the difficult choices presented by such major projects but the decision to cancel the Kemano Completion Project (KCP) rested on the provincial government’s reaction to southern pressures. Kemano, as with many major resource projects in northern regions, reveals the degree to which external political and commercial forces continue to determine northern development and therefore the very future of the region.